Behavior of Life Influenced by Drug Addiction on the Text of Drama ”A Prayer Before Dawn” - Yoga Agung Priambodo (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
The The behavior of human life is influenced by many things that we encounter in life, whether it is good or bad. that's what we will get according to what we live. sometimes we face those bad influences that are easier to enter into our lives, especially when we are in the teenage phase. Juvenile delinquency that generally occurs is about knowing something that has never been seen and done, such as drugs that are easily spread among teenagers today. Drugs are one of the major influences that can change human behavior for the worse, for example violence, robbery, murder, gambling, rape, and other bad things. Drugs cause hallucinations of people who consume them into a desire that must be fulfilled. Bad behavior that follows after prolonged drug consumption causes addiction which triggers to fulfill consumer needs which are mandatory and must be fulfilled for those who consume them. In research too see behavior of life influenced by drug on the drama text A Prayer Before Dawn (2017) by Jean-Stéphane Sauvaire using psychoanalytic theory by jacques lacan.